Impact of Extending the Timing of Maternal Pertussis Vaccination on Hospitalized Infant Pertussis in England, 2014–2018. (22nd June 2020) - Tessier, Elise; Campbell, Helen; Ribeiro, Sonia; Fry, Norman K; Brown, Colin; Stowe, Julia; Andrews, Nick; Ramsay, Mary; Amirthalingam, Gayatri
Abstract: Background: In October 2012, a maternal pertussis vaccination program was introduced in England for women between 28 and 32 weeks of pregnancy. In April 2016, the recommended optimal window was extended to 20–32 weeks to improve vaccine coverage and protect preterm infants. This study assesses the impact of offering maternal pertussis vaccination earlier in pregnancy on hospitalized infant pertussis cases. Methods: Hospitalized pertussis cases ≤60 days old in England were extracted from Hospital Episode Statistics pre- and post-policy change. Data were linked to laboratory-confirmed cases, and clinical records were reviewed where cases were not matched. Maternal vaccine status of identified cases was established. Median hospital duration was calculated, and a competing risk survival analysis was undertaken to assess multiple factors. Results: A total of 201 cases were included in the analysis. Of the 151 cases with reported gestational age, the number of hospitalizations among full-term infants was 60 cases pre-policy and 62 cases post-policy, respectively, while preterm cases declined from 20 to 9 ( P = .06). Length of hospital stay did not differ significantly after the policy change. Significantly longer hospital stays were seen in cases aged 0–4 weeks (median of 3 more days than infants aged 5–8 weeks), premature infants (median of 4 more days than term infants), and cases with coinfections (median of 1 more day than those without coinfection). Conclusions: The number of preterm infants hospitalized with pertussis in England was halved after the policy change and preterm infants were no longer overrepresented among hospitalized cases. Abstract : This study evaluates the impact of offering pertussis vaccination earlier in pregnancy in the second trimester on hospitalized infant pertussis cases in England. We found a decline in hospitalizations in preterm infants from 20 (18.5%) to 9 (9.7%) ( P  = .06).